Managing the Stress of War and Terrorism: Guidelines for Families - Suzanna Smith (EDIS)
War and terrorism are scary for children and families. Children of all ages may overhear adult conversations or see acts of war or terror on the news. These events are unsettling and stressful for children and their parents. Stress makes it hard to concentrate and go about daily routines. Stress that lasts a long time can hurt an individual’s and family’s health. On the other hand, children and their families can learn to be resilient in times of stress. They can bounce back from hard times, and become even stronger. This document is FCS9200, one of a series of the Department of Family, Youth and Community Sciences, Florida Cooperative Extension Service, IFAS, University of Florida, Gainesville FL 32611. First published: May 2003.